Dari Kultural Menuju Struktural - Perkembangan Nahdlatul Ulama di Kecamatan Manisrenggo, Klaten Tahun 1983-2017 - Sahid Wahyu Wijarnako; Latif Kusairi; Martina Safitry; Sucipto Sucipto (heritage, 2021)
Abstract Nahdlatul Ulama is a socio-religious organization founded by K.H. Hasyim Asy'ary with the elderly Kyai in East Java by carrying out the ideals of civilization, namely to create a harmonious and just world order based on morality. Manisrenggo is an area where people do not understand the teachings of Islam, so the majority of people still behave in violation of religious norms such as drinking, gambling, and believing in animism and dynamism. NU began to be known in Manisrenggo District around 1983 which was brought by K.H Masyhudi Hamid, a local Ulama from Wonokromo who moved to Klaten to carry out his duties as a Projo Pager or Satpol PP, as well as preaching to spread Islam to the Manisrenggo Community. This research uses the theory of great tradition and little tradition or big tradition and small tradition introduced by Robert Redfield. The results obtained from this study indicate that Manisrenggo which was originally a small area on the slopes of Mount Merapi where even the people know very little about Islam and their daily lives are still filled with activities that violate religious and community norms such as gambling, drinking, stealing, and others. After the arrival of Nahdlatul Ulama in Manisrenggo, the people became more acquainted with Islam and gradually began to know the teachings of Islam and leave their old culture. NU in Manisrenggo also plays an active role in social, religious, and educational fields which can be seen from the establishment of madrasas, Islamic boarding schools, TPAs, assemblies, mosques, prayer rooms, and various other activities with the community.